Analysis of Early Childhood Language Development Through the Use of Audio-Visual Media in Kindergarten (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Language is the effort of the mind and feelings to convey meaning to others which is used as a means of communication. Audio-visual media is a medium that can develop children's language skills. The purpose of this study is to find out how to develop children's language through audio-visual media in Ad-Dahlan Kindergarten, Sucinaraja District, Garut Regency. This research is a qualitative descriptive research involving 2 teachers and 20 children in class B1, data is collected through observation, interviews, analysis documents, data is analyzed qualitatively using data reduction, data display , and conclusion drawn. The results show that the teacher makes a learning implementation plan, the teacher studies the manual for the use of media, the teacher prepares and arranges the media equipment to be used, the teacher ensures that the media and all equipment are complete and ready to be used, the teacher explains the goals to be achieved, the teacher explains the material to the students before the activity takes place, the teacher conducts an evaluation. So all indicators of language development achievement can develop according to the level of development. The seven steps in the use of audio-visual media have been implemented by teachers at Ad-Dahlan Kindergarten, Sucinaraja District, Garut Regency and can be an alternative to develop early childhood language skills.